Direct Numerical Simulation of Turbulent Flows Containing Solid Particles - KAJISHIMA, Takeo (JAPANESE JOURNAL OF MULTIPHASE FLOW, 2017)
The turbulence modulation, that means influences of dispersed particles to the fluid turbulence, is one of the challenging subjects in the multiphase flow research. In recent decades, experimental and numerical researches have been conducted extensively. Especially the direct numerical simulation (DNS) became a powerful means to reveal the multiphase turbulence phenomena. But DNS cannot become a practical tool for multiphase flows in industry or in nature. In this review article, an example of particle-laden flow by the immersed solid method and our recent progress for the application to the two-phase heat transfer are shown. Then, considering the current status, it is pointed out that some moderately-averaged equation, which includes momentum exchange and residual stress terms, is essential for semi-DNS including finite-sized particles (e.g., Kolmogorov scale particle) to deal with large-scale multiphase flow fields.